AB0824 Improved Prediction of Hip Fracture Using the Health Assessment Questionnaire and FRAX in Japanese Patients with Rheumatoid Arhritis: A Prospective Observational Study. (10th June 2014) - Furuya, T.; Inoue, E.; Ochi, K.; Ishida, O.; Taniguchi, A.; Momohara, S.; Yamanaka, H.
Abstract : Background: The World Health Organization Fracture Risk Assessment Tool (FRAX®) algorithm can be used to estimate 10-year probabilities of hip and major osteoporotic fractures. This tool has not yet been validated in Japanese patients with rheumatoid arthritis (RA). Previously, we [1, 2] and others have reported a significant association between the Health Assessment Questionnaire Disability Index (HAQ-DI) and clinical fracture risk in patients with RA. This has generated interest in the possible role the HAQ-DI could play in improving fracture risk assessment for patients with RA [3]. Objectives: The aim of this study was to evaluate the prognostic accuracy of the Japanese version of FRAX to predict the 10-year probability of hip and major osteoporotic fractures in Japanese patients with RA, and investigate whether the HAQ-DI can further improve the prediction of hip and major osteoporotic fractures. Methods: We analyzed the database of the Institute of Rheumatology Rheumatoid Arthritis (IORRA) study, our large prospective observational cohort study in Japanese patients with RA. IORRA study subjects included 3, 095 women and 703 men with RA ranging in age from 40 to 90 years. The mean (± standard deviation) age was 60.6±9.6 years. Self-reported major osteoporotic fractures of the hip, vertebrae, humerus, and wrist were verified using patient medical records. The association of FRAX with fractures was evaluated by the Cox model, and C-statistics [4] were used in the risk prediction model to account for censored survival data. The Japanese version of HAQ-DI (J-HAQ-DI) was used in the assessment in conjunction with FRAX, without considering bone mineral density (BMD) values, and C-statistics were used for the 10-year risk calculated by the Cox model. Results: A total of 3, 798 Japanese patients with RA were followed for an average of 5.8 years. Using FRAX without BMD, the mean 10-year predicted fracture probability for hip and major osteoporotic fractures was 5.3% and 14.5%, respectively. Among the patients, 52 (1.4%) and 216 (5.7%) presented with hip and major osteoporotic fractures (including n=85 vertebral, n=41 humeral, n=38 distal radial, and n=52 hip fractures), respectively. For hip fractures, the C-statistic was 0.735 (95% CI: 0.665, 0.804) for the statistical model prediction based on both J-HAQ-DI and FRAX, and it was 0.688 (95% CI: 0.613, 0.762) for FRAX alone. For major osteoporotic fractures, the C-statistic was 0.678 (95% CI: 0.636, 0.719) for both J-HAQ-DI and FRAX, and 0.664 (95% CI: 0.624, 0.704) for FRAX alone. Conclusions: We evaluated the performance of FRAX in Japanese patients with RA using our prospective observational cohort study data. Our results were similar to those in other previously reported longitudinal studies evaluating FRAX. The HAQ-DI appears to improve hip fracture risk assessment when used in conjunction with this conventional risk assessment tool in patients with RA. References: Furuya T, et al. J Rheumatol. 2007; 34(2):303-10. Furuya T, et al. Osteoporos Int. 2013; 24(4):1257-65. Broy SB, et al. J Clin Densitom. 2011; 14(3):184-9. Uno H, et al. Stat Med. 2011; 30(10):1105-17. Acknowledgements: We thank all members of the Institute of Rheumatology, Tokyo Women's Medical University for the successful management of the IORRA cohort. This work was supported in part by grants-in-aid for scientific research from the Japan Osteoporosis Foundation to TF. Disclosure of Interest: T. Furuya: None declared, E. Inoue: None declared, K. Ochi: None declared, O. Ishida: None declared, A. Taniguchi: None declared, S. Momohara: None declared, H. Yamanaka Grant/research support: Abbott, AbbVie, Asahikasei, Astellas, AstraZeneca, Bristol-Myers Squib, Chugai, Daiichi Sankyo, Eisai, GlaxoSmithKline, Janssen, Mitsubishi Tanabe, MSD, Nippon Kayaku, Pfizer, Santen, Taishotoyama, Takeda, Teijin, Consultant for: Abbott, AbbVie, Astellas, AstraZeneca, Bristol-Myers Squib, Chugai, Daiichi Sankyo, Eisai, Mitsubishi Tanabe, Nippon Kayaku, Pfizer, Takeda, Teijin, Speakers bureau: Abbott, AbbVie, Astellas, Bristol-Myers Squib, Chugai, Eisai, Mitsubishi Tanabe, Pfizer, Takeda, Teijin DOI: 10.1136/annrheumdis-2014-eular.1579